Conservation of archaeological copper alloy artifacts from Al Ain National Museum collection: the role of desalination - Lois Carrera, Diego; Vieira, Eduarda; Bosetto, Eleonora (Ge-conservacion, 2020)
Al Ain National Museum is in the city of Al Ain, within the Emirate of Abu Dhabi, United Arab Emirates. This museum preserves an excellent collection of copper alloy archeological objects from different archeological sites around Al Ain all dated from the Neolithic era. We have observed a high concentration of chloride salts in most objects, which favors their corrosion. We conjecture that this may be the case for most sites located in arid zones near the coast.This paper aims to highlight the desalination treatments used during the conservation project of these artifacts. Desalination was the central treatment to achieve their stabilization and to promote their preservation for as long as possible. While the B70 desalination system has proven to be quite effective; salts still remain on the objects. Therefore, relative humidity and temperature monitoring are required to avoid variations that could reactivate sealed chlorides inside the objects.